Impact Toughness of Isothermally Treated Duplex Stainless Steels. Issue 1616 (25th February 2014) - Calliari, I.; Breda, M.; Straffelini, G.; Miranda Perez, A. F.; Reyes Valdes, F. A.
ABSTRACT: Duplex stainless steels (DSS) have good mechanical and corrosion resistance properties which allow their application in very aggressive environments. However, their aging at 600–1000 °C causes the precipitation of dangerous intermetallic phases, resulting in serious detrimental effects on their interesting properties. These secondary phases are structural discontinuities which act as preferential cracks initiation sites and their negative effect is especially highlighted on toughness. For these reasons, many standards related to the manufacturing of DSS require the microstructure of these steels "free from intermetallics". In this paper, the effect of isothermal heat treatments on the impact toughness in two Duplex steels (SAF 2205 and Zeron®100) has been investigated, in order to study the influence of different amount of secondary phases on the toughness response.